Description of Learningg Outcomes, Misconceptions, and Inhibitory Materials, and Their Relationship With The Implementation of The Scientific Approach - Aslamiah Al Anshori; Zonalia Fitriza (Entalpi Pendidikan Kimia, 2022)
The 2013 curriculum requires the application of scientific approach in learning. As many as 53.84% of the 13 chemistry teachers in West Sumatra experienced difficulties in implementing scientific approach cause the limited time allocation and low student learning outcomes.This study aims to describe learning outcomes, misconceptions, and inhibitory materials and the relationship between the implementation of the scientific approach to the chemical bonding material. This descriptive research uses Mixed Method with Convergent mixed parallel design. The population is the students of X class SMA in Pasaman Regency with sample of class X MIPA. Data were collected using document analysis, observation methods, and tests. The data were analyzed using the Miles & Huberman analysis technique, normality test, and correlation test. The results of this study indicate that the scientific approach has not been implemented properly. Student learning outcomes <4% and as many as 61 types of misconceptions were identified cause the presence of inhibitory materials such as atomic stability for chemical bonds, PEI and PEB for molecular geometry, and Lewis structures for intermolecular interactions. The results of the analysis concluded that there was a correlation between the implementation of the scientific approach and learning outcomes with a significance of 0.00 and a correlation coefficient of 0.617. So, the implementation of the scientific approach affects student learning outcomes.